The effect of the addition of silanized Nano titania fillers on some physical and mechanical properties of heat cured acrylic denture base materials - Alwan, Sama A; Alameer, Shatha S (Journal of Baghdad College of Dentistry, 2015)
Background: Polymethyl methacrylate (PMMA) is the most commonly used material in denture fabrication. The material is far from ideal in fulfilling the mechanical requirement. The purpose of this study was to evaluate the effect of addition of 3% wt of treated (silanized) Titanium oxide Nano filler on some physical and mechanical properties of heat cured acrylic denture base material. Materials and methods: 100 specimens were constructed, 50 specimens were prepared from heat cure PMMA without additives (control) and 50 specimens were prepared from heat cure PMMA with the addition of TiO2 Nano fillers. Each group was divided into 5 sub groups according to the test performed which was mixed by probe ultra-sonication machine. Results: A highly significant increase in impact strength and transverse strength was observed with the addition of (TiO2) Nano particles to (PMMA). A significant increase in surface hardness and in surface roughness. The water sorption and solubility were significantly decreased when compared with the control group. Conclusions: The addition of TiO2 Nano particles to heat cure acrylic resin improve the impact strength, transverse strength and surface hardness of heat cure acrylic resin at the same time this addition decrease water sorption and solubility. On the other hand there was an increase in surface roughness with the addition of 3% wt of silanized TiO2 Nano particles. Keywords: NanoTiO2, TMSPM, PMMA.